The Utility of Micro-R/Hypo-He Ratio Cut-off for Distinguishing Iron Deficiency Anemia and Minor Thalassemia - Audiyananda, Dwika; Prihatni, Delita; Surata, Nida; Sugianli, Adhi Kristianto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Thalassemia is a genetic disease with impaired synthesis of the globin chain that causes anemia. Thalassemia and Iron Deficiency Anemia (IDA) are both microcytic hypochromic anemia but have different proportions of hypochromic and microcytic erythrocytes due to differences in disease mechanisms. Research parameters of the hematology analyzer: %Micro-R, %Hypo-He, and MH ratio can be used as early screening for thalassemia and IDA. This study aimed to evaluate the cut-off of %Micro-R, %Hypo-He, and MH ratio to differentiate thalassemia from IDA. A cross-sectional study was carried out on 217 subjects. Subjects were divided into two groups, thalassemia and IDA based on hemoglobin electrophoresis, hematology examination, and Mentzer index. Differences and cut-off values of %Micro-R, %Hypo-He, and MH ratio between the two groups were analyzed. The number of collected data was 134, consisting of 89 thalassemia patients and 45 IDA patients. Thalassemia patients had a median %Micro-R value of 51.2 (4.3-79.0), %Hypo-He value of 7.2 (0.2-50.2), and MH ratio of 7.17 (1.10-64.50), higher than IDA patients (p=0.000; p=0.176; p=0.000). The optimal cut-off value for %Micro-R in discriminating thalassemia trait from IDA was >12.7, with the area under the ROC curve (AUC) of 0.945, sensitivity of 92.1%, and specificity of 82.2%. The cut-off value for MH ratio > 3.27 with AUC 0.833, sensitivity of 85.4%, and specificity 77.8% showed lower performance of cut-off value compared to %Micro-R. The algorithm using %Micro-R and MH ratio was proposed for thalassemia trait screening. High %Micro-R and MH are suggestive of thalassemia trait than of IDA.